Cysticercus pisiformis-derived novel-miR1 targets TLR2 to inhibit the immune response in rabbits - Chen, Guoliang; Pu, Guiting; Wang, Liqun; Li, Yanping; Liu, Tingli; Li, Hong; Zhang, Shaohua; Wang, Xuelin; Liu, Xiaolei; Luo, Xuenong (Frontiers in Immunology, 2023)
Cysticercosis pisiformis, a highly prevalent parasitic disease worldwide, causes significant economic losses in the rabbit breeding industry. Previous investigations have identified a novel microRNA, designated as novel-miR1, within the serum of rabbit infected with Cysticercus pisiformis (C. pisiformis). In the present study, we found that C. pisiformis-derived novel-miR1 was released into the rabbit serum via exosomes. Through computational analysis using Targetscan, miRanda and PITA, a total of 634 target genes of novel-miR1 were predicted. To elucidate the functional role of novel-miR1, a dual-luciferase reporter assay was utilized and demonstrated that novel-miR1 targets rabbit Toll-like receptor 2 (TLR2). Rabbit peripheral blood lymphocytes (PBLCs) were transfected with novel-miR1 mimic and NC mimics, and the in vitro experiments confirmed that novel-miR1 suppressed the expression of pro-inflammatory cytokines such as TNF-α, IL-1β, and IL-6 though the NFκB pathway. In vivo experiments demonstrated that novel-miR1 was significantly up-regulated during the 1 to 3 months following infection with C. pisiformis in rabbits.Notably, this up-regulation coincided with a down-regulation of TLR2, P65, pP65, TNF-α, IL-1β, and IL-6 in PBLCs. Collectively, these results indicate that the novel-miR1 derived from C. pisiformis inhibited the rabbits' immune response by suppressing the NFκB mediated immune response. This immune modulation facilitates parasite invasion, survival, and establishment of a persistent infection.